Bacteriology of peritonsillar abscess: the changing trend and predisposing factors - Tsai,Yi-Wen (2018)
Abstract Introduction: Peritonsillar abscess is the most common deep neck infection. The infectious microorganism may be different according to clinical factors. Objective: To identify the major causative pathogen of peritonsillar abscess and investigate the relationship between the causative pathogen, host clinical factors, and hospitalization duration. Methods: This retrospective study included 415 hospitalized patients diagnosed with peritonsillar abscess who were admitted to a tertiary medical center from June 1990 to June 2013. We collected data by chart review and analyzed variables such as demographic characteristics, underlying systemic disease, smoking, alcoholism, betel nut chewing, bacteriology, and hospitalization duration. Results: A total of 168 patients had positive results for pathogen isolation. Streptococcus viridans (28.57%) and Klebsiella pneumoniae (23.21%) were the most common microorganisms identified through pus culturing. The isolation rate of anaerobes increased to 49.35% in the recent 6 years (p = 0.048). Common anaerobes were Prevotella and Fusobacterium spp. The identification of K. pneumoniae increased among elderly patients (age > 65 years) with an odds ratio (OR) of 2.76 (p = 0.03), and decreased in the hot season (mean temperature > 26 °C) (OR = 0.49, p = 0.04). No specific microorganism was associated with prolonged hospital stay. Conclusion: The most common pathogen identified through pus culturing was S. viridans, followed by K. pneumoniae. The identification of anaerobes was shown to increase in recent years. The antibiotics initially selected should be effective against both aerobes and anaerobes. Bacterial identification may be associated with host clinical factors and environmental factors.